PERBANDINGAN TERAPI BERMAIN FINGER PAINTING DAN PUZZLE TERHADAP PERKEMBANGAN MOTORIK HALUS ANAK RASEKOLAH DI SLEMAN - Nur Khasanah; Melania Wahyuningsih; Uswatun Hasanah (Jurnal Penelitian, 2022)
The prevalence of children experiencing fine motor delays in Indonesia according to the Ministry of Health of the Republic of Indonesia in 2018, reached 11.7%. Fine motor delays can cause impaired coordination of hand and eye movements, so they can interfere with children's creativity and skills. There are many ways that can be done to prevent fine motor delays, including by providing therapy to play finger painting and puzzles, but some people do not know this. Based on the results of the preliminary studies, it is known that of 10 children, 6 of them had deviations and 4 children were in the dubious category. Objective: Knowing The Comparison Of Finger Painting And Puzzle Play Therapy To Fine Motor Development Of Preschool Age Children Research Methods: research method quasi experiment design. Design two group posttest only nonequivalent control group. Population 42 and Sample of 32 preschool children using accidental sampling techniques, KPSP instruments and standard operational procedures (SOP). Results: The average fine motor score in the puzzle group was 9.50 while the average fine motor score in the finger painting group was 7.50. with a P-value of 0.000. Conclusion: there was a significant difference of the average postest value of the puzzle group by 23.12 points higher than the finger painting therapy of 9.88 points.